Modification of poly(dimethylsiloxane) as a basis for surface wrinkle formation: Chemical and mechanical characterization. (19th August 2016) - Campo, Adolfo del; Nogales, Aurora; Ezquerra, Tiberio A.; Rodríguez-Hernández, Juan
Abstract: In this manuscript, the processes occurring during UV-ozone treatment on polydimethylsiloxane (PDMS) surfaces i.e. formation of a stiff silica-like layer and surface degradation have been studied. While the chemical changes have been evaluated using Confocal Raman Microscopy (CRM) with submicrometer resolution, partial surface degradation occurring during longer ozone treatments have been evidenced both by Optical Profilometry and AFM. Whereas previous studies reported the formation of a thin silica layer of around 20–30 nm up to 200 nm depending on the method employed, herein, we demonstrated that in effect a thin rigid layer is formed but instead of a sharp interface predicted by previous reports a gradient depth profile was obtained. CRM evidenced the formation of a 4 μm layer of modified material. By Quantitative Nanomechanical Mapping (QNM) and based on the equations that predict the wrinkle formation, a surface layer thickness of around of 4.5 μm was also determined. Graphical abstract: Highlights: The mechanisms involved in the UVO surface treatment on PDMS were investigated. The simultaneous degradation/functionalization of PDMS surfaces was demonstrated. Confocal Raman evidenced the formation of a gradient surface modification. The functionalization depth varies between 1 and 5 μm depending on the UVO exposure.